A evolução da indenização por acidente do trabalho - Freudenthal, Sérgio Henrique Pardal Bacellar (2006)
This paper looks over the Labor Accident Indemnity s Evolution, mainly inside the Brazilian Legislation. It goes through the doctrinaire view of its law assemblages, and examines their interpretations. It analyses the Labor Accident Doctrines and their applications until our present days, giving particular attention to the Federal Constitution, and its disposition on Labor Accident Indemnity. Labor Accident and Professional Diseases deserve much more attention than just suggesting the establishment of an indemnity pay for the damage caused. Dignity and better work conditions, with all the technology available nowadays, should be put up to the service of mankind. Those are Fighting Symbol of Workers Unions throughout the World, which does not take away the importance of the indemnity owned for the worker, who has suffered Labor Accident, reduced labor capacity sequela. Indemnity is very important, not just because of the Social Security refunds, therefore insuring some compensation for the worker s reduced labor capacity, in addition to its necessary note for Statistics, but also because of its implied Civil Responsibility, when the condemnation has a pedagogic character as well. Therefore, Labor Accident Indemnity is a subject that deserves special attention. Its historical study begins with the Industrial Revolution, goes through the Doctrine s evolution and our National Legislation, until the present conditions of the Labor Accident Laws, their present text application, with all the modifications done on the last decade, and the making of a future text in order to regulate Labor Accident Social Security Services as is established on the Constitutional Emend nº 20/98, not only by Government Social Security Service but by Private Security Companies as well. Its developed research has based itself on the National and Foreigner Doctrines, both Traditional and Modern, as well as on Legislation and Jurisprudence , including writings and data found on periodic magazines. This theme brings up huge debates, since our present political moment has already been demanding a bigger consideration from our Courts, on the search of a more favorable Law consolidation and its application in favor of those who work. It also demands the attention of the Legislation Assembly in the making of more equal laws, therefore contributing not only to a more rich Society, with higher and more productive technology, but also to a more just one